2009
DOI: 10.1162/jocn.2009.21104
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Learning Modifies Perceptual Face Processing

Abstract: Abstract& Face processing changes when a face is learned with personally relevant information. In a five-day learning paradigm, faces were presented with rich semantic stories that conveyed personal information about the faces. Event-related potentials were recorded before and after learning during a passive viewing task. When faces were novel, we observed the expected N170 repetition effect-a reduction in amplitude following face repetition. However, when faces were learned with personal information, the N170… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
23
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 43 publications
5
23
1
Order By: Relevance
“…The authors compared processing of unfamiliar faces with processing of newly learned faces that either had been associated with a name and a piece of biographical information or had been learned in isolation without any accompanying information. In contrast to the observations by Galli et al (2006) and Heisz and Shedden (2009), Paller and colleagues found an influence of biographical knowledge on recognition performance in an old/new judgement task. While no N170 effects were reported, the authors demonstrated an enhanced positivity at frontal electrodes between 400 and 500 ms after stimulus presentation to faces associated with biographical information, relative to faces presented without information.…”
contrasting
confidence: 59%
See 1 more Smart Citation
“…The authors compared processing of unfamiliar faces with processing of newly learned faces that either had been associated with a name and a piece of biographical information or had been learned in isolation without any accompanying information. In contrast to the observations by Galli et al (2006) and Heisz and Shedden (2009), Paller and colleagues found an influence of biographical knowledge on recognition performance in an old/new judgement task. While no N170 effects were reported, the authors demonstrated an enhanced positivity at frontal electrodes between 400 and 500 ms after stimulus presentation to faces associated with biographical information, relative to faces presented without information.…”
contrasting
confidence: 59%
“…This result indicates that there might be knowledge effects on ERP components that are associated with processes normally considered to be impenetrable by semantic knowledge. Likewise, Heisz and Shedden (2009) demonstrated that the N170 repetition effect (an amplitude decrease with repetitions) was present only for unfamiliar faces, but absent for faces that were familiar (in the sense that participants acquired semantic information about the faces).…”
mentioning
confidence: 91%
“…Such a view seems to be supported by the greater false alarm rate associated with reward-related faces. Several lines of research have recently shown effects of familiarity, repetition priming, and recognition on N170 responses to faces (Caharel, Courtay, Bernard, Lalonde, & Rebai, 2005;Campanella et al, 2000;Guillaume et al, 2009;Heisz & Shedden, 2009;Herzmann & Sommer, 2010;Jacques & Rossion, 2006;Jemel et al, 2005;Jemel et al, 2003;Marzi & Viggiano, 2007, 2010a, 2010b, suggesting that, as early as 170 ms after stimulus onset, the brain is individuating previously encoded faces. In line with these studies, we further suggest that reward-related processes might interact with structural encoding processes that lead to face recognition.…”
Section: Reward-related Recognition Memorymentioning
confidence: 99%
“…The N170 is generally viewed as a marker of the encoding stage of the face structure (Eimer, 2000;Rossion et al, 1999), when the perceptual representation of a face is being created, although its sensitivity to identity is still actively debated (e.g. Caharel et al, 2009;Heisz and Shedden, 2009;Schweinberger., in press, 2010).…”
Section: Introductionmentioning
confidence: 99%